Isolation and characterization of the positive regulatory gene ADR1 from Saccharomyces cerevisiae. - Denis, C L (Mol Cell Biol, 1983)
The DNA segments containing the ADR1 gene and a mutant allele, ADR1-5c, have been isolated by complementation of function in Saccharomyces cerevisiae. The ADR1 gene is required for synthesis of the glucose-repressible alcohol dehydrogenase (ADHII) when S. cerevisiae cells are grown on a nonfermentable carbon source, whereas the ADR1-5c allele allows ADHII synthesis even during glucose repression. A plasmid pool consisting of yeast DNA fragments isolated from a strain carrying the ADR1-5c allele was used to transform a strain containing the adr1-1 allele, which prevents ADHII depression. Transformants were isolated which expressed ADHII during glucose repression. A plasmid isolated from one of these transformants was shown to carry the ADR1-5c allele by its ability to integrate at the chromosomal adr1-1 locus. The wild-type ADR1 gene was isolated by colony hybridization, using the cloned ADR1-5c gene as a probe. The ADR1-5c and ADR1 DNA segments were indistinguishable by restriction site mapping. A partial ADR1 phenotype could be conferred by a 1.9-kilobase region, but DNA outside of this region appeared to be necessary for normal activation of ADHII by the ADR1 gene. IMAGES: